Confirmatory Factor Analysis of Strength Awareness Scale in a Sample of Indonesian Female Leaders - Dhania, Dhini Rama; Susanti, Ruth Natalia (Psympathic : Jurnal Ilmiah Psikologi, 2023)
This study aimed to test psychometric properties of strength use scale (SUS) as a unidimensional concept with 14 question items on a sample of female leaders who work in two manufacturing companies. The investigation, the subjects used consisted of 521 females in management positions at various levels. Confirmatory Factor Analysis (CFA) was applied to analyze the factor validity of the unidimensional SUS consisting of 14 items. Additionally, Indonesian version of SUS was validated using a confirmation approach. In line with previous studies, the analysis confirmed the unidimensionality of the scale, which measures a singular strength through factors. The demands on internal consistency, composite reliability, and convergent validity were met. The results showed that Indonesian version of SUS is comparable to the original English version, representing a valid and reliable measure of strength used in Indonesian. Therefore, future studies should consider adding subjects with different sociodemographic backgrounds.